Achieving optimum carrier concentrations in p-doped SnS thermoelectrics. Issue 14 (11th March 2015) - Bhattacharya, Sandip; Gunda, N. S. Harsha; Stern, Robin; Jacobs, Stéphane; Chmielowski, Radoslaw; Dennler, Gilles; Madsen, Georg K. H.
Abstract : Tin(ii )sulfide, SnS, is a commercially viable and environmentally friendly thermoelectric material. This work is a comprehensive guide to achieve effective p-doped SnS. Abstract : Tin(ii )sulfide, SnS, is a commercially viable and environmentally friendly thermoelectric material. Recently it was shown how the carrier concentration and the thermoelectric power factor can be optimized by Ag-doping in a sulphur rich environment. Theoretical calculations lead to a fairly accurate estimation of the carrier concentration, whereas the potential of doping with Li + is strongly overestimated. Two principally ubiquitous effects that can result in decreasing the hole concentration, namely the formation of coupled defect complexes and oxidation of the dopant, are discussed as possible origins of this disagreement. It is shown that oxidation limits the chemical potential of Li beyond that already set by the formation of Li2 S. This work serves as a comprehensive guide to achieve an efficient p-doped SnS thermoelectric material.